Teste das microbolhas estáveis no aspirado bucal de recém-nascidos prematuros para o diagnóstico de síndrome do desconforto respiratório - Ribeiro, Manoel Antonio da Silva (2016)
BACKGROUND: The stable microbubbles test on the gastric aspirate has been used for the diagnosis of respiratory distress syndrome of the newborn. However, its use in the preterm newborn oral aspirate was not determined. OBJECTIVE: To evaluate the performance of the stable microbubbles test done on oral aspirate from preterm newborns to predict of respiratory distress syndrome. METHOD: In the study were included infants with gestational age < 34 weeks. Oral secretion sample was obtained immediately after birth and gastric secretion was collected within 30 minutes of life. The samples were frozen and tested within 72 hours. RESULTS: The sample was composed of paired secretion of 70 newborns. The median (interquartile range) of the stable microbubbles count in the oral samples of infants with respiratory distress syndrome was significantly lower than those who did not develop or had respiratory symptoms from other causes: 12 (8 - 22) versus 100 (48 - 230) versus 70 (44 - 208) (p <0.01). The correlation between microbubble count in gastric and bucal aspirates was 0.88 (95%CI: 0,72 – 0,93; p <0.01). Taking a cut-off point of 15 microbubbles/mm2, the sensitivity of test was 95.4%, the specificity 66.7%, and the agreement of the oral fluid with the gastric fluid was 0.76. CONCLUSION: The study suggests that the stable microbubbles test in gastric aspirate made at birth is a reliable alternative to the gastric fluid in the prediction of respiratory distress syndrome of the newborn.